Pengaruh Pengaruh Self-control dan Intensitas Penggunaan E-wallet terhadap Perilaku Manajemen Keuangan Mahasiswa: Perspektif Frictionless Payment - Melda Dea Safitri; Nurul Aini; Mega Zhafarina Purwono (CV. ITTC INDONESIA, 2026)
With the introduction of e-wallets, student purchasing patterns are evolving in tandem with advancements in digital payment technology. The convenience of transactions provided by seamless payment systems may have an impact on students' money management habits, particularly if they lack sufficient self-control. . Therefore, more research is required to ascertain how students' financial management practices are influenced by their amount of e-wallet usage and self-control. This study aims to investigate the impact of self-control. , the level of digital wallet usage, and the combined effect of these two factors on students' financial management behavior from the standpoint of frictionless payments. This study uses a quantitative methodology with an explanatory research approach and a cross-sectional design. Students who actively utilize e-wallets for everyday transactions make up the research population. One hundred respondents were chosen as the sample using purposeful sampling. Primary data was gathered using a Likert-scale questionnaire, and multiple linear regression analysis was performed using IBM SPSS Statistics 25. Additionally, these two factors have a positive and significant influence when combined, with an F-value of 55.103 and a significance level of 0.000. The results of this study show that self-control. has a favorable and significant impact on students' financial management behavior, with a t-value of 7.078 and a p-value of 0.000. The frequency of e-wallet use also has a positive and substantial impact, with a t-value of 3.996 and a significance level of 0.000.